Susret - Bezinovic, Igor (Croatia, 2009)
Film about the encounter that occurred on the day of the Corpus Christy Feast in 2009 in Vukovarska Street in Zagreb when the students from the Faculty of Humanities and Social Sciences came to support the farmers’ protests in front of the Ministry of Agriculture building. The euphoric student’s night and the sobering farmer’s day; the media aware activism and the heavy machinery on the streets; plenum democracy and the quarreling farmers’ associations are just some of the radically different aspects of this unlikely alliance which reveals so much about contemporary society in Croatia.
Verzio Film Festival Submission
Keywords: Documentary films